2007
DOI: 10.5194/angeo-25-1827-2007
|View full text |Cite
|
Sign up to set email alerts
|

Maps of <I>fo</I>F2, <I>hm</I>F2, and plasma frequency above F2-layer peak in the night-time low-latitude ionosphere derived from Intercosmos-19 satellite topside sounding data

Abstract: Abstract. Maps of foF2, hmF2, and plasma frequency, fp, in the topside ionosphere at low latitudes, derived from Intercosmos-19 satellite topside sounding data, obtained from March 1979 to January 1981 and covering all longitudes, are presented for quiet geomagnetic conditions in June and December solstices at solar maximum for several local time intervals during the night. Based on these maps, features of the equatorial anomaly (EA) at different longitudes and their change during the night are considered. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…We note that the presence of the wavelike density structure was identified earlier by topside soundings from the Russian satellite Intercosmos‐19 [ Kochenova , 1987, 1988; Karpachev , 1988; Benkova et al , 1990; Karpachev et al , 2003; Deminova , 2003, 2007]. The daytime morphologies of the upward drift velocity, electric field, and equatorial electrojet that were calculated using the latitudinal profile of the F peak electron density [ Benkova et al , 1990] showed a good agreement with the recent observations.…”
Section: Introductionsupporting
confidence: 85%
“…We note that the presence of the wavelike density structure was identified earlier by topside soundings from the Russian satellite Intercosmos‐19 [ Kochenova , 1987, 1988; Karpachev , 1988; Benkova et al , 1990; Karpachev et al , 2003; Deminova , 2003, 2007]. The daytime morphologies of the upward drift velocity, electric field, and equatorial electrojet that were calculated using the latitudinal profile of the F peak electron density [ Benkova et al , 1990] showed a good agreement with the recent observations.…”
Section: Introductionsupporting
confidence: 85%